2006
DOI: 10.2169/internalmedicine.45.6074
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serological Tests Detecting Chlamydophila pneumoniae-specific Immunoglobulin M Antibody

Abstract: Object. To evaluate a newly developed enzyme-linked immunosorbent assay (ELISA) (Hitazyme C. pneumoniae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 16 publications
1
10
0
2
Order By: Relevance
“…Index values ≥1.60 were defined as positive for IgM antibody, and values ≥1.10 were defined as positive for IgA or IgG antibodies. Increases of 1.0 in the index value for IgA and 1.35 in the index value for IgG between paired sera were also defined as positive 16 …”
Section: Methodsmentioning
confidence: 99%
“…Index values ≥1.60 were defined as positive for IgM antibody, and values ≥1.10 were defined as positive for IgA or IgG antibodies. Increases of 1.0 in the index value for IgA and 1.35 in the index value for IgG between paired sera were also defined as positive 16 …”
Section: Methodsmentioning
confidence: 99%
“…In Japan, a kit using a purified chlamydial outer membrane complex as the antigen (HITAZYME C. pneumoniae; Hitachi Chemical Co. Ltd., Tokyo, Japan) has been widely used [5], and IgM antibody measurement has been covered by the national health insurance since 2005. However, the positive rate is unexpectedly high, and negative conversion does not occur for a prolonged period when the current diagnostic criteria of C. pn primary infection in children (IgM ID C1.1) is applied, which can be problematic [6]. In this study, we re-evaluated the diagnostic criteria of primary infection involving children with airway symptoms, and investigated the prevalence of the infection employing the new criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an RFabsorbing reagent is used in the MySet test and no crossreactions have been detected. In addition to RF, we suggested that chronic lung diseases such as chronic obstructive pulmonary disease, collagen disease-associated interstitial lung disease, and cryptogenic organizing pneumonia may cause falsepositive reactions for IgM with another enzyme-linked immunosorbent assay kit (8). However, no patients with chronic lung disease or high levels of RF were included in the present study, and we could not determine the cause of the false-positive reaction in the MySet test.…”
mentioning
confidence: 73%